The legal protection system of indigenous peoples in Southeast Asia - Aditya, Zaka Firma; Al-Fatih, Sholahuddin (Faculty of Law, University of Muhammadiyah Malang, 2023)
Globalization has a bad impact on the indigenous peoples in Southeast Asia countries. The demands of globalization have led the governments in Southeast Asia countries to exploit and industrialize indigenous regions excessively, resulting in marginalized indigenous peoples and the threat of extinction. Not intended for the benefit and welfare of indigenous peoples, the policy made by the government in several Southeast Asia countries did much to reduce the value of humanity and the rights of indigenous peoples. Even with rapid industrialization in Southeast Asia countries, many indigenous peoples are poor, left far behind, and illiterate due to isolation from the outside world. This paper aims to analyze the legal protection of indigenous people in Southeast Asia, especially in facing digital age. By normative juridical method, this paper found that the government and developers' exploitation of indigenous peoples in the region has always been laden with conflicts between the government, the developers (economic motive), and indigenous peoples, and such conflicts of interest are usually won by the interests of the government and/or developers. Indigenous peoples' right to sue for damages caused is sometimes hampered with difficulty simply because the government holds powerful and dominant standing in courts. Moreover, most countries in the Southeast Asia region does not have customary courts in their judicial institution.